Dental management of children with cerebral palsy - a review - Milind Wasnik; Shweta Chandak; Suryakant Kumar; Miranda George; Niharika Gahold; Durga Bhattad (Wolters Kluwer Medknow Publications, 2020)
According to American Academy of Pediatric Dentistry (AAPD), special health-care needs (SHCN) is "any physical, developmental, mental, sensory, behavioral, cognitive, or emotional impairment or limiting condition that requires medical management, health-care intervention, and/or use of specialized services or programs." Oral health is an inseparable part of general health. Throughout the lifetime, individuals with SHCN may be at a greater risk for oral diseases. The aim of this article is to discuss the dental management of children with cerebral palsy (CP) in detail. Children with SHCN have a considerably higher prevalence of oral diseases as compared to otherwise healthy children. The role of the pediatric dentist is to improve oral health wellness and to encourage parents and caregivers for good home oral health practice. This article will help the dentist to understand all the aspects related to the dental management of patients with CP and apply it in clinical practice.